2021
DOI: 10.3389/fbioe.2021.569045
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of IgG1 Producing CHO Cells Using LC/LC-SPS-MS3: The Effects of Bioprocessing Conditions on Productivity and Product Quality

Abstract: The biopharmaceutical market is dominated by monoclonal antibodies, the majority of which are produced in Chinese hamster ovary (CHO) cell lines. Intense cell engineering, in combination with optimization of various process parameters results in increasing product titers. To enable further improvements in manufacturing processes, detailed information about how certain parameters affect cellular mechanisms in the production cells, and thereby also the expressed drug substance, is required. Therefore, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We hypothesize that this heterogeneity arises from the use of different expression host cells and/or different culture conditions (temperature, pH, CO 2 concentration, time, bioreactor size, etc.) in the bioprocesses that may tune the glycosylation profile and the C-terminal lysine variants of these biotherapeutics [53][54][55]. However, despite the molecular heterogeneity of the proteoforms observed in the two biotherapeutics, no clinical differences between the two drugs in terms of toxicity were observed when prescribed for the treatment of diffuse large B-cell lymphoma [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this heterogeneity arises from the use of different expression host cells and/or different culture conditions (temperature, pH, CO 2 concentration, time, bioreactor size, etc.) in the bioprocesses that may tune the glycosylation profile and the C-terminal lysine variants of these biotherapeutics [53][54][55]. However, despite the molecular heterogeneity of the proteoforms observed in the two biotherapeutics, no clinical differences between the two drugs in terms of toxicity were observed when prescribed for the treatment of diffuse large B-cell lymphoma [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…[ 26–28 ] A wide range of proteomics techniques such as tandem mass tag (TMT), isobaric tags for relative and absolute quantitation (iTRAQ), and Sequential Windowed Acquisition of All Theoretical Fragment Ion Mass Spectra (SWATH‐MS) have been used to explore the impact of bioprocessing changes on CHO cells. [ 29–35 ]…”
Section: Introductionmentioning
confidence: 99%
“…Riboflavin metabolism is known to be involved in mitochondrial beta-oxidation, and is therefore essential for energy production within the cells [ 23 ]. Apart from the necessity of energy production to maintain cell viability, it has also been shown that energy metabolism plays an important role during recombinant protein expression [ 5 ]. In the past, cellular production systems have been greatly engineered in order to modify cell metabolism, aiming towards higher specific productivity rather than biomass production [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting observation is the activation of oxidative phosphorylation. As mentioned before, we have shown previously that increased recombinant protein productivity in CHO cells can be achieved upon a higher level of oxidative phosphorylation [ 5 ]. Cellular energy metabolism can easily be targeted by changes in the bioprocessing conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation